2021
DOI: 10.3390/ijms22158265
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of the Association between HLA-G Expression by Carcinomas and Clinical Outcome

Abstract: Human leukocyte antigen-G (HLA-G) conveys immunological tolerance at the maternal-foetal interface. HLA-G expression by tumour cells may also play such a role, resulting in tumour immune evasion, making HLA-G a potential target for immunotherapies. The aim of this review was to determine to what extent it is justified that HLA-G expression is considered as a target for immune checkpoint inhibiting therapy by critically assessing the association between HLA-G expression by carcinomas and clinical outcome of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…It is now widely accepted that HLA-G is a critical marker of immunotolerance in cancer immune evasion and is strongly associated with disease progress and prognosis in cancer patients. However, not all published works are equally consistent and, although they show HLA-G expression in cancer, do not allow to correlate HLA-G with certain types of cancer (81).…”
Section: Limitation Of Hla-g Expression Analysis In Tissuesmentioning
confidence: 92%
See 1 more Smart Citation
“…It is now widely accepted that HLA-G is a critical marker of immunotolerance in cancer immune evasion and is strongly associated with disease progress and prognosis in cancer patients. However, not all published works are equally consistent and, although they show HLA-G expression in cancer, do not allow to correlate HLA-G with certain types of cancer (81).…”
Section: Limitation Of Hla-g Expression Analysis In Tissuesmentioning
confidence: 92%
“…The other problem lies in the methodological approaches employed. The vast majority of HLA-G detection studies use immunohistochemistry as the main method, but each laboratory uses different antibodies and variable experimental conditions (incubation times, antibody concentration, etc), even when analyzing the same type of tumor (81)(82)(83). In addition, some of these antibodies used, such as the 4H84 clone, appear to be poorly specific for HLA-G detection (84).…”
Section: Limitation Of Hla-g Expression Analysis In Tissuesmentioning
confidence: 99%
“…The loss of HLA also occurs in LUAD, and the proportion of occurrence is not low ( Dejima et al, 2021 ). But at the same time, we also noticed that the research of van de Water et al (2021 ) showed that the expression level of HLA-G was inconsistent with the prognosis of lung cancer, but the prognosis and HLA-G level of patients with breast cancer, esophageal cancer, gastric cancer, and hepatocyte maintained a good correlation. This is in common with our findings and contradicts them, implying that the mutational diversity of HLA molecules has the value for further study.…”
Section: Discussionmentioning
confidence: 82%
“…HLA-G interacts with NK cell killer Ig-like receptors (KIRs), resulting in the inhibition of NK cells [164]. Consistently, HLA-G expression in various malignancies was associated with tumour escaping immunosurveillance and was also involved in the mechanism of metastasis, leading to poor clinical outcomes [165].…”
Section: Immunosuppressive Cytokines Present In the Tmementioning
confidence: 98%